Physical and Organoleptic Characteristics of Non Gluten Macaroni from Composite Flour (Tapioca, Rice, and Corn) with Xanthan Gum Addition - Shalsabiella, Shafira Enri; Yulistiani, Ratna (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2025)
Macaroni is a widely popular pasta product traditionally made from durum semolina wheat flour, which contains high levels of gluten. In this study, gluten-free macaroni was developed using alternative flour sources. The objective of this study was to evaluate the effects of different proportions of tapioca flour, rice flour, and corn flour, along with the addition of anchovy flour and xanthan gum, on the physical (rehydration capacity and cooking loss) and organoleptic (color, aroma, taste, and texture) characteristics of gluten-free macaroni. A factorial Completely Randomized Design (CRD) with two factors and two replications was used. Factor I was the proportion of tapioca flour, rice flour, and corn flour (55:35:10 g, 60:20:20 g, and 65:5:30 g). Factor II was the xanthan gum concentration (1%, 2%, 3%). If a significant difference was detected, further analysis was conducted using Duncan’s Multiple Range Test (DMRT) at a 5% significance level, followed by a hedonic organoleptic evaluation using the Friedman test. The results demonstrated a significant interaction between flour composition and xanthan gum concentration on rehydration capacity, which ranged from 100.52% to 105.47%, and cooking loss, which averaged between 1.28% and 3.19%. Organoleptic evaluation revealed significant differences in color and texture, while taste and aroma were not significantly affected. These findings suggest that optimizing flour composition and xanthan gum concentration can enhance the quality of gluten-free macaroni, providing an alternative for individuals with gluten intolerance. Contribution to Sustainable Development Goals (SDGs):SDG 2: Zero Hunger by promoting the diversification of food sources, SDG 3: Good Health and Well-Being) by providing a gluten-free alternative beneficial for individuals with gluten intolerance, SDG 12: Responsible Consumption and Production by utilizing locally available, nutrient-rich ingredients such as anchovy flour. Developing gluten-free macaroni not only supports dietary diversity but also contributes to sustainable food production and improved public health.